2023
DOI: 10.2298/psi220416004w
|View full text |Cite
|
Sign up to set email alerts
|

Job autonomy and employee strengths use: The roles of work engagement and job insecurity

Abstract: Employee strengths use has been found to be beneficial to employee and the employer organization. Yet, we have little knowledge on the antecedents to employee strengths use. participants (N = 241). Results indicate that psychopathy, narcissism and marital dissatisfaction are related to stronger tendencies towards infidelity, and that these effects are partially (in the case of psychopathy and marital dissatisfaction) or totally (in the case of narcissism) mediated by the tendency to morally j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
(97 reference statements)
0
1
1
Order By: Relevance
“…Specifically, when role overload is high, employees’ social resource (i.e., strengths-based leadership) will be depleted, which in turn, leads employees to have less social resource enhance organizational identification and consequently leads to lower levels of OCB. Although previous research has found that job insecurity (Wang & Ding, 2023) and job autonomy (Ding & Yu, 2022) can moderate the effect of strengths-based leadership, this study identified a new boundary condition of the effectiveness of strengths-based leadership. Thus, this study advances our understanding of the effectiveness of strengths-based leadership.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Specifically, when role overload is high, employees’ social resource (i.e., strengths-based leadership) will be depleted, which in turn, leads employees to have less social resource enhance organizational identification and consequently leads to lower levels of OCB. Although previous research has found that job insecurity (Wang & Ding, 2023) and job autonomy (Ding & Yu, 2022) can moderate the effect of strengths-based leadership, this study identified a new boundary condition of the effectiveness of strengths-based leadership. Thus, this study advances our understanding of the effectiveness of strengths-based leadership.…”
Section: Discussioncontrasting
confidence: 56%
“…Alongside the emergence of strengths-based approaches, strengths-based leadership has gradually triggered researchers’ interest (Wang & Ding, 2023). Strengths-based leadership refers to a series of behaviors that leader executes to promote followers’ strengths identification, development, and use (Ding & Yu, 2020).…”
Section: Theory and Hypothesesmentioning
confidence: 99%